Deportation vs. Sanctuary: The Rationalities, Technologies, and Subjects of Finnish Sanctuary Practices - Pyykkonen, Miikka (Refuge (Toronto. English edition), 2009)
Evangelical Lutheran parishes and their representatives have provided sanctuaries for asylum seekers for forty years in Finland. Yet this activity became widely publicly recognized only after the Finnish Ecumenical Council released the “Church as Sanctuary” document in 2007. The parishes are assisted by many civic organizations (e.g. women’s organizations, Free Movement Network, Amnesty International, and Finnish Refugee Council) in providing sanctuary. They share the same opponent: the state’s strict asylum policy. The various parties involved in Finnish sanctuary incidents can be divided into two groups using the terminology of the Foucaldian analytics of pastoral power: a state pastorate and the civic/church pastorate. The former tries to secure the vitality of its “flock,” the Finnish population, through strict control over asylum seekers. The latter pastorate challenges the state’s sovereignty to define its accepted members by offering alternative ways for asylum seekers to stay in the country and an alternative understanding of who this “flock” should include. In this article I analyze how these parties construct their subjectivities and the asylum-seeker’s subjectivity in the sanctuary incidents. Despite seeming opposition between the two pastorates, there are similarities in the ways by which they seek to clarify the inner soul-life of the asylum seekers and make them knowable and governable. Les paroisses évangéliques luthériennes de Finlande et leurs partenaires fournissent le sanctuaire aux demandeurs d’asile depuis quarante ans. Pourtant, cette activité n’a été largement reconnue publiquement qu’après la publication en 2007 du document Kirkko turvapaikkana (L’église refuge) par le conseil œcuménique de Finlande. Les paroisses sont assistés par de nombreuses organisations civiques (p. ex., organisations féminines, réseau Libre circulation (Vapaa liikkuvuus), Amnistie internationale, conseil Finlandais pour les réfugiés) en fournissant l’asile. Elles partagent un même adversaire: la politique rigoureuse de l’État sur l’asile. Les parties impliquées dans des cas de sanctuaire en Finlande peuvent être divisés en deux groupes selon la terminologie de l’analyse foucaldienne du pouvoir pastoral: le pastorat étatique et le pastorat civique/chrétien. Le premier cherche à assurer la vitalité de son « troupeau », la population finlandaise, à travers un contrôle strict sur les demandeurs d’asile. En offrant aux demandeurs d’asile des solutions de rechange pour rester au pays et une autre compréhension de la composition de ce « troupeau », le second met en cause le droit souverain de l’État de définir ses membres acceptés. Dans cet article, j’analyse comment ces parties construisent leurs subjectivités et la subjectivité du demandeur d’asile dans les cas de sanctuaire. Malgré une opposition apparente entre les deux pastorats, il y a des similarités dans la manière par laquelle tous deux cherchent à purifier l’âme humaine des demandeurs d’asile et à rendre ceux-ci connaissables et gouvernables.